Blood Pressure Reduction, Decreased Diffusion on MRI, and Outcomes After Intracerebral Hemorrhage - Garg, Rajeev K (2011)
BACKGROUND: Decreased diffusion (DD) consistent with acute ischemia may be detected on MRI after acute intracerebral hemorrhage (ICH), but its risk factors and impact on functional outcomes are not well defined. We tested the hypotheses that DD after ICH is related to acute blood pressure (BP) reduction and lower hemoglobin (HGB) and presages worse functional outcomes. METHODS: Patients who underwent MRI were prospectively evaluated for DD by certified neuroradiologists blinded to outcomes. HGB and BP data were obtained via electronic queries. Outcomes were obtained at 14 days and 3 months with the modified Rankin Scale (mRS), a functional scale scored from 0 (no symptoms) to 6 (dead). We used logistic regression for dependence or death (mRS 4 to 6). RESULTS: DD distinct from the hematoma was found on MRI in 36 of 95 patients (38%). DD was associated with greater BP reductions from baseline, and a higher risk of dependence or death at 3 months (OR 4.8, 95% CI 1.7 – 13.9, P=0.004) after correction for ICH Score (1.8 per point, 95%CI 1.2–3.1, P=0.01). Lower HGB was associated with worse ICH score, larger hematoma volume and worse outcomes, but not DD. CONCLUSIONS: DD is common after ICH, associated with greater acute BP reductions, and associated with disability and death at 3 months in multivariate analysis. The potential benefits of acute BP reduction to reduce hematoma growth may be limited by DD. The prevention and treatment of cerebral ischemia manifested as DD is a potential method to improve outcomes.